Extra credit for disruption: trend of disruption in radiology academic journals. Issue 12 (December 2022) - Abu-Omar, A.; Kennedy, P.; Yakub, M.; Robbins, J.B.; Yassin, A.; Verma, N.; Scaglione, M.; Khosa, F.
Abstract : AIM: To identify the most disruptive publications, which are those that are cited more frequently than their own references, in academic radiology journals and their characteristics, such as the number of authors and relative time to publication. MATERIAL AND METHODS: A comprehensive literature search was undertaken to identify the 100 most disruptive publications in the field of radiology. Subsequently, statistical analysis was applied to establish the distribution of disruptive scores of the isolated publications using a non-parametric probability density function. The relation between disruptive scores and citation counts was then determined, with the aid of a correlation coefficient. Finally, data regarding any significant connection between disruption scores and time of publication, number of authors, and study design were examined. RESULTS: Analysing the top 100 papers in increments of 10-year periods showed no significant difference in the distribution of disruption scores over time. No correlation between an article's citation count and disruption score was established. Additionally, no significant relation between the number of authors/study design and disruption scores was identified. CONCLUSION: The disruption score highlights significant impact elements not entirely accounted for by citation count. Its potential benefit in assessing scientific impact should be contemplated. Highlights: Article citation count has been criticized for its unreliability. Article disruption score highlights significant impact elements not accounted for by citation count or journal impact factor. Disruption score maybe a useful metric and consideration should be given to its broader use in assessing scientific impact.